Kelengkapan Fasilitas Wisata Di Greengrass Cikole - Kahla, Hanifa Fahri Fadhilla; Nugraha, Rizki Nurul; Fitriani, Dina; Hutahaean, Jhon Irvan Fadli; Trisia, Putri Adinda (Jurnal Ilmiah Wahana Pendidikan, 2023)
Camping is one of the activities that is the goal of everyone who wants to relieve fatigue by enjoying the beautiful natural scenery while staying in that place. One of these tourist destinations is Greengrass located in Lembang, Bandung. A camping site that offers a cool natural atmosphere and various facilities needed by visitors. This study aims to find out what facilities are located in Greengrass Cikole and what facility planning will be carried out. The research method used is by descriptive research method through direct observation and observation of the object of research. The results obtained from this study where the management has plans for facilities and accessibility ranging from toilets to road repairs which are still a shortcoming for Greengrass Cikole tourist destinations.